Respiratory and storage behavior of fresh cut 'Tommy Atkins' mango - Souza, B. S. [UNESP]; Durigan, J. F. [UNESP]; Donadon, J. R. [UNESP]; Teixeira, G. H A [UNESP]; Durigan, M. F B [UNESP] (My University, 2005)
The respiratory and storage behavior of fresh cut 'Tommy Atkins' mango, naturally ripened (NR) or with use of ethylene (RE), were studied. Fruits were selected, washed and disinfected (200 mgCl.L-1) and stored for 12 hours at 10°C. After this period, they were processed under hygienic conditions at 10°C, packaged in polyethylene terephthalate (PET) trays or in styrofoam trays wrapped with stretchable polyvinyl chloride (PVC) film and stored for up to 15 days at 3°C. The products were evaluated regarding the evolution of internal atmosphere in the packing (O2 and CO 2), development of weight, appearance, shelf life and consumer acceptability. The respiratory rate was measured before and after processing every two hours. The yield of 'Tommy Atkins' mango to produce fresh cut product was 48.09±0.95%. Increase of the respiration rate of both mango samples was verified one hour after the preparation (NR = 17.75 mL CO 2.kg-1.h-1; RE = 28.29 mL CO 2.kg-1.h-1), followed by stabilization at 3.76 and 8.07 mL CO2/kg.h, respectively. The percentage of O2 in packages was stable in all treatments, 15-20% in PVC trays, 18-20% in PET tray. The percentage of CO2 was steady around 1.5-2.5%. The products lost fresh mass during the storage, from 0.06% to 0.30% for PET trays and from 0.15% to 1.61% for trays covered with PVC. The appearance was considered appropriate for commercialization until the 13th day, whereas product from mangoes ripened with application of ethylene was for 11 days, presenting browning in the external surface. The naturally ripened mango presented the best flavor and consumer preference in relation to the mango ripened with application of ethylene for 11 days of storage. The control of hygienic conditions during the production and storage was good and with safety for until 10 days.
Keywords: Mangifera indica L.; Minimally processed; Package; Quality; Shelf life